The Role of Public Health Interventions in Sustainable Food Systems: Fostering Healthier and Resilient Communities through Nutritional Strategies - Andi Hardianti; Levon Galstyan; Michel Augustin (Journal of Multidisciplinary Sustainability Asean, 2026)
Background. The sustainability of food systems is increasingly threatened by environmental, economic, and social pressures, impacting nutritional security and public health outcomes. Malnutrition, dietary imbalances, and foodborne illnesses remain persistent challenges that compromise community resilience. Public health interventions play a critical role in addressing these issues by promoting healthy dietary practices, strengthening food safety measures, and fostering systemic resilience within food production and distribution networks. Purpose. This study aims to evaluate the effectiveness of targeted public health interventions in enhancing sustainable food systems and improving community nutrition outcomes. The research seeks to identify key strategies that mitigate health risks, support equitable access to nutritious foods, and promote long-term resilience in vulnerable populations. Method. A mixed-methods approach was employed, integrating quantitative surveys on dietary behaviors, nutritional indicators, and food access with qualitative case studies from selected communities. Data were collected from 200 households, local health authorities, and food distribution networks, and analyzed using statistical modeling and thematic content analysis to assess intervention outcomes. Results. Findings indicate that communities receiving integrated public health interventions experienced significant improvements in dietary diversity, reduced prevalence of nutritional deficiencies, and enhanced adherence to food safety protocols. Interventions that combined education, policy support, and community engagement were most effective in fostering sustainable nutrition outcomes. Conclusion. The study concludes that coordinated public health strategies are essential for building resilient, healthier communities and ensuring the long-term sustainability of food systems. These findings provide actionable insights for policymakers, public health practitioners, and food system stakeholders.